Muslim Business Women in Indonesia - Farihatul Qamariyah (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study examines the intersection between religion and economic performance through investigating religious ethics and tradition among devout businesswomen. This study also focuses on the issue of spiritual business enterprise. I observed seven Muslim business women as subjects who negotiate a religious and cultural perception of their gendered role in society. During their entrepreneurial journey, Muslim business women transform their conventional company into spiritual – based operations for religious and ethical reason. I undertook nine weeks of fieldwork in urban areas of Jakarta, Purworejo and Yogyakarta. I also conduct life story interview sessions and participatory observation with the seven Muslim business women’s project of business including director, manager, employee, and so – called spiritual division. Significantly, the products that they sell reflect spiritual and moral underpinnings. Moreover, the spiritual design of company plays a role in employee screening, training, and benefit, which all incorporate aspects of Islamic practice. This research demonstrates the strong role of religion namely Islam, as evidenced in the Muslim business women’s narratives, in functioning as a support system that can greatly enhance the economic and life prosperity. Keywords: Muslim business women, religious ethics, spiritual economics, Indonesia